"Do I Live in a Flood Basin?": Synthesizing Ten Thousand Maps - Elias, Miguel; Elson, Jeremy; Fisher, Danyel; Howell, Jon (Proceedings of the 2008 Conference on Human Factors in Computing Systems (CHI), 2008)
The recent introduction of simple, web-based geographic visualization interfaces has unleashed a tidal wave of new geographic content now available on the Internet. There has been enormous attention on the development of data interchange standards and programming interfaces that make all this content interoperable, but far less thought about how the user experience should change when users have their choice of 10,000 maps. To inform the design of online mapping systems, we investigate the case of queries that require correlation of multiple maps—that is, discovery and synthesis of several map layers. We based our study on interviews with expert users of maps: archivists and librarians. This paper describes our user-task taxonomy distilled from these interviews, and presents MapSynthesizer, a prototype system that allows users to efficiently query, discover, and integrate many maps from a corpus of thousands.
Demo and download at http://research.microsoft.com/mapcruncher/MapSynthesizer/